Determining the Association between Preeclampsia and the Thyroid Hormone Status in Pregnant Women - Salari, Saeideh; Zamani, Saeed; Raesi, Rasoul; Hushmandi, Kiavash; Daneshi, Salman (Current Women's Health Reviews, 2025)
BackgroundPreeclampsia is a significant multisystem disorder in pregnancy care that hormonal, environmental, and genetic factors can cause.AimThis study aimed to investigate the relationship between preeclampsia and thyroid hormone levels in pregnant women.MethodsThis case-control study was conducted in 2022 with 200 pregnant women in southeast Iran, utilizing a convenience sampling method. The participants included 100 women in the preeclampsia group and 100 in the normal pregnancy group. Data related to preeclampsia were obtained from the Integrated Health System (SIB) at the health center in Jiroft city, while information about the thyroid hormones was extracted from the Ministry of Health's SIB system. The data were analyzed using SPSS-26 software, employing both descriptive and inferential statistical tests.ResultsSystolic pressure was significantly higher in the preeclampsia group (149.14 mmHg) than in the control group (105.33 mmHg), and diastolic pressure also showed a significant difference (94.57 mmHg in preeclampsia vs. 64.33 mmHg in normal pregnancies). Thyroid-stimulating hormone (TSH) levels were significantly higher in the preeclampsia group (3.7) compared to the normal pregnancy group (2.5), indicating a notable difference (p<0.005). Thyroid thyroxine (TT4) levels were significantly lower in the preeclampsia group (10.78) compared to the control group (12.5) (p<0.005).ConclusionThyroid function significantly impacts the risk and severity of preeclampsia, with elevated TSH and reduced TT4 levels indicating potential complications. Monitoring these hormone levels is crucial for managing affected pregnancies. It is recommended that health policymakers include thyroid function screening in prenatal care protocols.
Keywords: pregnancy